Radiation to Chemicals Unpacking Occupational Safety Hazards in Educational Hospital through the HOSHRA Lens - Kavi Magsoudhi; Abbasi Haghighat (Inovasi Analisis Data, 2024)
Objective: The current study evaluates occupational safety and health risks in educational hospitals using the Hoshra index by concentrating on the detection and control of frequent hazards.Methods: Using a structured approach, the HOSHRA index classifies risks in to physical, chemical, biological, ergonomic and psychological domains. The framework supports targeted risk scoring, improving the efficiency with which hospitals can allocate resourcesFindings: The analysis uncovers important types of healthcare worker hazards. Biological and psychological risks appear to be particularly suboptimal, emphasizing the importance of effective infection control interventions, as well as psychological care. The study underscores the need to have a culture of safety that supports hazard reporting and management.Novelty: This is one of the first to use the HOSHRA index in many educational hospital, introducing new methods for risk analysis and assessment beyond traditional classic styles.Research Implications: The results highlight the need for adapted and risk based strategies in healthcare settings. Healthcare organizations can improve the well-being of staff and, by extension, patient care outcomes, by aligning safety protocols with the unique features of wards.